THE INFLUENCE OF A GENERATIVE LEARNING MODEL BASED ON WAVE MATERIAL COGNITIVE CONFLICT ON STUDENT LEARNING OUTCOMES AT SMAN 5 PAYAKUMBUH - akmam, akmam; Agustin, Novia (Physics Learning and Education, 2024)
Student learning outcomes in Physics subjects, especially in Wave material, are still low. This is caused by the learning model used in the Wave material not being being the process standards and characteristics of wave learning objectives. A generative learning model based on cognitive conflict is one approach to solving the aforementioned issue. The purpose of this study is to ascertain how student learning outcomes at SMAN 5 Payakumbuh are affected by the use of a generative learning model based on cognitive conflict in Wave content. The type of research is quasi-experimental research with a pretest-posttest Control Group Design. The participants in this study were all SMAN 5 Payakumbuh science class XI students. The information gathered reflects the attitudes, knowledge, and abilities of the pupils toward learning. Two averages are tested for equality as a data analysis technique. The study's findings demonstrate the notable distinctions between classrooms that employ the Problem-Based Learning model and those that employ the Generative learning model based on cognitive conflict. The average student learning outcome in classes that apply the Generative learning model is 83.14 and in classes that apply the Problem-Based Learning model is 77.26. The influence of the generative learning model based on cognitive conflict can be seen in the learning outcomes of students who have been analyzed and hypothesis tested. Based on the hypothesis test, the ttable is 2.006 and the tcount is 2.1. The condition for H0 to be rejected is if ttable < tcount. The tcount value is within the rejection of H0, so HI is accepted. Because all variables are controlled, except the learning model, it can be said that the application of the Generative learning model based on cognitive conflict in Wave material has a positive effect on student learning outcomes.